Contribuição para. o conhecimento da "saúva parda" Atta capiguara Gonçalves, 1944 - Mariconi, Francisco A. M.; Zamith, Adiel P. L.; Castro, Urbano de Paiva (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1961)
This paper deals with field investigations on the biology of "saúva parda" (brown parasol ant, Atta capiguara Gonçalves, 1944), performed at Piracicaba and several other counties (State of São Paulo, Brazil). This ant is very noxious to several grasses and seems to make its colony only in very poor soils. Formerly the insect was known only in three counties; the writers found it in other fourteen ones.